Enhancing the efficiency process for separation of dry shell and palm kernel - Mohd Iezany, Rosli (2013)
Palm oil Processing Palm kernel is one of the products from palm oil mills. In kernel recovery plant, the separation of kernel and shell from cracked mixture is carried out using a combination of dry and wet separation. The objective of this study were to enhance the efficiency process for separation of dry shell an palm kernel as well as to maximizing the recovery of dry kernel and shell based on the installation of four stage winnowing column. This user friendly and compact separation device uses forced draught principle instead of the usual induced draught. The air flow velocity in each separating column can be adjust via the blower (damper) located at the ground or an elevated level. The effect of velocity and fan air speed in activity of separation must take in consideration. The parameter that has been monitored during the trials was dirt & shell content in production kernel, kernel losses and effect of velocity on efficiency of separation. The system was also equipped with a unit of a small vibro clay bath to minimize the kernel losses by recovering the very fine kernel pieces generated from the screw press. The system was capable separate drier kernel shell. The total kernel loss from dry and wet separation also could be minimized. This four stage winnowing system also reduces the waste effluent from the mill promoting more environmental friendly technology for the oil palm industry.